An integrative model of knowledge sharing in Malaysian Higher Learning Institute - Fauri @ Fauzi, Muhammad Ashraf; Nya-Ling, Christine Tan; Thurasamy, Ramayah; Ojo, Adedapo Oluwaseyi (Emerald Group Publishing Ltd., 2018)
Purpose – This paper aims to understand the factors that can determine the knowledge sharing (KS) intention and behaviour of academics in Malaysian higher learning institutes (HLIs), thus affecting academics research productivity. Design/methodology/approach – The study’s respondents were 525 academics from public and private HLI in Malaysia. This study adapts theory of planned behaviour (TPB) and social capital theory (SCT) to determine academics KS intention and behaviour of academics and the factors that can influence along the KS process. Findings – Results indicate that among the factors of academics KS behaviour, there are two factors that are not significant, commitment and perceived cost, while the rest showed significant results. The strongest factors are management support and social media use among academics. The result also shows that academics intention to share is explained by 62.1 per cent of the variance, while academics KS behaviour is explained by 47.1 per cent of the variance. Research limitations/implications – This study shows the high intention and behaviour of sharing among Malaysian academics and suggests that academics in this country are cautious and aware of the importance of knowledge for human capital and development of nation. Practical implications – This paper facilitates university in hiring academics that support KS activities. Originality/value – The integration of TPB and SCT in evaluating Malaysian academics KS behaviour can eventually affect the research productivity. Furthermore, addition of several variables, such as perceived cost, facilitating conditions make this study a holistic model to predict academic research performance.